Innovations in home energy use A sourcebook for behavior change - Southwell, Brian G.; Doran, Elizabeth M. B.; Richman, Laura S. (RTI Press Publication, 2016)
As a collection of essays that explore innovations to encourage reduction in homeowner energy use, this volume reflects a confluence of ideas and initiatives rather than a narrow look at what a single, particular line of academic literature suggests might be possible to shape homeowner behavior. Not only do the contributors represent a wide array of institutions and backgrounds, but the very intellectual infrastructure that encouraged and allowed the summit that inspired this book itself represents a conscious effort to facilitate multidisciplinary and interdisciplinary collaboration for the purpose of addressing salient societal concerns. With this volume, we hope to provide a source of ideas for behavior change that will appeal to a range of people charged with curbing residential energy use through communication-based intervention.